Statistical and synoptic analysis of cold waves in North West of Iran - yousouf ghavidel rahimi; manochehr farajzadeh asl; solmaz motalebizad (تحقیقات کاربردی علوم جغرافیایی)
This study tries to identify, classify, and analyze synoptic cold wave in North West region of Iran. This study applies standardized (z scores) index of Minimum Temperature in the period of 1951-2010.as such cold waves were classified based on the intensity of occurance. Out of occured cold wave in North West of the coldest identified wave pertaingt each class for synoptic analyzes were selected. This study suggests that the prevailing pressure pattern during the relevant wave indicates high pressure over the earth surface as well as deep trough in upper layer. From the continuing cold standpoint, the role of changing position from pavallel wind in to meridional corresponel to blocking is very offective. Blocking in turn leads to reduction in speed of cold air masses which are originating from higher latitude. They were assouclated with cold waves. More precipitation as so ciated with higher latitude as well as low speed flows will lead to strong and continious waves.